Influence on intraocular lens power calculation of corneal radii measurement using an image-guided system - Thomas, Bettina C.; Müller, Andreas; Auffarth, Gerd U.; Holzer, Mike P. (Journal of cataract and refractive surgery, 2016)
Purpose - To analyze the influence on intraocular lens (IOL) power calculation of corneal radii measured by the Verion Image-Guided System in comparison with those measured by partial coherence interferometry (PCI) (IOLMaster) and optical low-coherence reflectometry (OLCR) (Lenstar) systems. - Setting - International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - Design - Prospective case series. - Methods - One eye of ophthalmologically healthy volunteers was examined with the image-guided, PCI, and OLCR systems. Corneal radii could be measured with all 3 devices; axial length (AL) and anterior chamber depth (ACD) could be measured with PCI and OLCR only. The IOL power calculations for the Acrysof SN60WF IOL using 4 formulas were compared between the image-guided system and both the PCI device and OLCR device. For IOL calculation with the image-guided system, the AL and ACD of the device used for comparison were applied. - Results - Of the 150 volunteers, 136 (mean age 39.60 years ± 17.31 [SD]) had valid measurements with all 3 devices and were included in the analysis. Compared with PCI, the image-guided system measured statistically significant larger values for corneal radii and IOL power calculations for all 4 formulas. There were no statistically significant differences between the image-guided system and the OLCR device. In both groups, the surgeon would have chosen the same IOL power in approximately 60% to 65% of cases and a ±0.5 diopter different IOL power in approximately 30% to 35% of cases when using the image-guided system. - Conclusions - The IOL power calculation using the image-guided system showed statistically significant differences compared with the PCI device but not when compared with the OLCR device. The clinical relevance of this theoretical approach remains to be evaluated. - Financial Disclosure - Drs. Auffarth and Holzer received travel grants and lecture fees from Alcon Pharma GmbH and Carl Zeiss Meditec AG.
Gesehen am 27.05.2020